Technologies for active aging - Sixsmith, Andrew; Gutman, Gloria (International perspectives on aging, 2013)
The two phenomena are occurring side by side: a rapidly growing elder population and a burgeoning tech sector. Where a few years ago these worlds would not have met, a new generation of older adults has grown comfortable with technology and open to its possibilities for improving their lives as they age.  Technologies for active aging offers novel answers to a range of aging issues, from safety and mobility to cognition and continence. Written for the non-technical reader, the book examines the potential of information and communicative technologies such as pervasive computing, smart environments, and robotics to enhance seniors' quality of life and encourage independent living, better care and self-care, and social participation. Diversity is emphasized here, in terms of the life areas addressed, the perspectives of elders and caregivers, and the global reach of those working toward solutions. This state-of-the-field volume looks ahead to future research and the next wave of innovations to help all seniors, regardless of health or ability. Among the topics featured: Promoting technology use by people with dementia. Wheelchair mobility in older adults. Intelligent systems for assessing age-related changes using home-based technology. Measuring the effectiveness of assistive technologies in community and home settings. Technology for the prevention of fall-related injuries. tele-health in chronic disease management.  A comprehensive mix of theoretical developments and emerging realities, technologies for active aging serves a variety of professionals, including gerontologists, sociologists, health and cross-cultural psychologists, and public health policymakers.